Pyruvate Kinase M2 Promotes Prostate Cancer Metastasis Through Regulating ERK1/2-COX-2 Signaling - Guo, Wenjing; Zhang, Zhishuai; Li, Guihuan; Lai, Xiaoju; Gu, Ruonan; Xu, Wanfu; Chen, Hua; Xing, Zhe; Chen, Liping; Qian, Jiabi; Xu, Shiyuan; Zeng, Fangyin; et al. (Frontiers in Oncology, 2020)
Pyruvate kinase M2 (PKM2) is a key enzyme of glycolysis which is highly expressed in many tumor cells, and has emerged as an important player in tumor progression and metastasis. However, the functional roles of PKM2 in tumor metastasis remain elusive. Here we showed that PKM2 promoted prostate cancer metastasis via ERK-cyclooxygenase (COX-2) signaling. From public databases, we found that PKM2 expression was upregulated in prostate cancer and positively associated with tumor metastasis. We demonstrated that PKM2 promoted prostate cancer cell migration/invasion and epithelial-mesenchymal transition (EMT) through upregulation of COX-2. Mechanistically, PKM2 interacted with ERK1/2 and regulated its phosphorylation, and these kinases regulate phosphorylation of transcription factor c-Jun to activate COX-2 expression. Finally, we confirmed that Inhibition of COX-2 activity prevented tumor metastasis induced by overexpression of PKM2 in vivo. Our results suggest that PKM2-ERK1/2-c-jun-COX-2 axis is a potential target in controlling prostate cancer metastasis.